Synthesis and characterisation of graphene and its corrosion resistance on magnesium alloys - Muhammad Azim Anwar, Noor Hisham (2021)
Magnesium is one of the lightest structural metal is greatly used in many applications. Due to its good biodegradability and mechanical properties, magnesium alloys are considered as the ideal candidate for the cardiovascular stents. The rapid degradation in human physiological environment and the poor biocompatibility seriously limit its application for biomaterials. Its hexagonal close packed structure of magnesium has lowered the ductility of it and it is poor corrosion resistance in aqueous electrolyte. In order to maximize the corrosion resistance of magnesium, some research had be done on it as multilayer coating has carry out by dip coating method. Coating a layer of high corrosion resistance material on it is one of the most simple and economic way. Graphene has emerged and known as one of the strongest, thinnest, and lightest material in the world which is very suitable used as a coating material to improve corrosion resistance of magnesium. There are many methods can be used in synthesising graphene but not all could be used in producing it in bulk quantities. The method used for huge scale of high quality graphene production usually demands high costing, high-skilled and requires high energy. Electrochemical exfoliation is believed to be one of the potential method to overcome this problem as it is easy to conduct at low. The aim of this study is to evaluate the effect of different solvents in sonication process on the formation of graphene from the electrochemical exfoliation of graphite. Graphite rod was exfoliated by electrochemical process with ammonium sulfate as salt-electrolyte. The exfoliated powder then sonicated under two different solvents, which are dimethylformamide (DMF) and aqueous solution to form graphene. Both type of solvent produced similar structure of graphene. The microstructures of exfoliated graphene were carefully characterized under field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) characterization. The successful graphene produced was then coated by using dip-coating method to test the corrosion properties of magnesium. The amount of graphene produced was different due to the differences in graphene stability. Graphene is more stable in DMF solvents compared to the aqueous solution as resulted in UV-Vis Spectroscope. The aqueous solution can allow the reversible reaction that can reform graphite oxide from graphene due to the existence of hydroxyl component in the aqueous solution. The DMF solvents used to help in achieving the second objective by study the effect of graphene coating on corrosion properties of magnesium. The potentiodynamic polarization curve showed that the coating of graphene had improved the corrosion resistance of magnesium alloy. The 7 layers of coating presents an ideal result of corrosion rate with 0.2944 mA/cm2, while 5 layers and 9 layers shows 2.234 mA/cm2and 0.9940 mA/cm2respectively. In conclusion, this research was able to prove that the graphene coating on the magnesium AZ31B alloy was able to increase the graphene coating and corrosion properties of the magnesium itself.